VALUE-BASED LEARNING IN LITERARY EDUCATION THROUGH THE INTERPRETATION OF SUNDANESE PROVERBS TO PROMOTE SOCIAL CHANGE - Ristiani, Iis (Prosiding Konferensi Internasional Kesusasteraan, 2025)
Value-based learning in literary education plays a crucial role in shaping students’ character and social awareness. This study aims to analyze the interpretation of Sundanese proverbs as a medium for value-based learning that can be integrated into literary education to promote social change. Using a qualitative research design with a literary ethnography approach, data were collected through documentation studies, interviews, and classroom observations in higher education. The findings reveal that Sundanese proverbs embody social values such as mutual cooperation, honesty, hard work, and tolerance, which can be effectively implemented in literary learning to enhance students’ social awareness and critical thinking. The implications of this study emphasize the importance of revitalizing local wisdom through literary education as a strategy for character building and fostering social transformation in educational contexts.